The Protective Role of Religiosity Against Quarter-Life Crisis Among Final-Year University Students - Devika Dian Afrilia; Royanulloh (Journal of Religious Studies, 2025)
Purpose: This study aims to examine the protective role of religiosity in mitigating the symptoms of quarter-life crisis among final-year university students. The transition from academic life to early adulthood often triggers emotional instability, anxiety, and uncertainty regarding future careers and identity formation. Religiosity is hypothesized to serve as a psychological buffer that fosters resilience, meaning, and self-regulation during this critical life stage. Method: A correlational quantitative approach was employed involving 112 final-year students aged 18–29 from a public Islamic university in Indonesia. Data were collected through standardized questionnaires measuring religiosity and quarter-life crisis dimensions, and analyzed using Pearson’s product–moment correlation to assess the association between variables. Findings: Results revealed a significant negative correlation between religiosity and quarter-life crisis (r = –0.212, p < 0.05). Students with higher levels of religiosity reported lower levels of emotional confusion, anxiety, and hopelessness about their future. The findings indicate that spiritual beliefs, religious practices, and internalized moral values contribute to stronger coping mechanisms when facing transitional stressors. Significance: The study underscores the importance of integrating spiritual development into higher education counseling programs to support students’ psychological well-being. By highlighting religiosity as a protective factor, this research enriches the global discourse on the interplay between faith and mental health in emerging adulthood. Future research is encouraged to explore longitudinal patterns and cross-cultural perspectives to deepen understanding of this relationship.